2022
DOI: 10.3390/pr10050881
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Methylation of C6-8~Arene with Methanol: Mechanism, Catalysts, Kinetic/Thermodynamics and Perspectives

Abstract: High-efficiency production of xylene/trimethylbenzene from benzene/toluene with methanol is a potential way to promote the implementation on the coupled cycle development strategy of petrochemical and coal chemical industry and optimize the resource structure. At the same time, relying on the innovation of catalytic new materials, physical chemistry, intelligent capture technology, process engineering, and other principles and methods, p-xylene (PX) and trimethylbenzene (TMB) with higher added value were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…This type of carbon is expected to be produced from the MTO reaction since the light ole ns produced from the reaction could further react to form higher ole ns, para ns, aromatics, and naphthenes through hydrogen transfer reaction or aromatization (Stö 1999;Olsbye et al 2012). These hydrocarbons nally condense to form carbon deposition, which is usually seen as lamentous carbon deposition (Dong et al 2022). On the basis of the above results, it is concluded that the synthesized FSAPO-34 displays a high resistance toward coke deposition, which leads to high catalytic stability in the MTO reaction due to the formation of brous silica on SAPO-34.…”
Section: Analysis Of Spent Catalystsmentioning
confidence: 99%
“…This type of carbon is expected to be produced from the MTO reaction since the light ole ns produced from the reaction could further react to form higher ole ns, para ns, aromatics, and naphthenes through hydrogen transfer reaction or aromatization (Stö 1999;Olsbye et al 2012). These hydrocarbons nally condense to form carbon deposition, which is usually seen as lamentous carbon deposition (Dong et al 2022). On the basis of the above results, it is concluded that the synthesized FSAPO-34 displays a high resistance toward coke deposition, which leads to high catalytic stability in the MTO reaction due to the formation of brous silica on SAPO-34.…”
Section: Analysis Of Spent Catalystsmentioning
confidence: 99%
“…However, the acidic sites on the surface of the ZSM-5 grain are non-selective in the activation and transformation of hydrocarbon molecules. In addition to the transformation to aromatics, the light hydrocarbons diffused to the surface of the ZSM-5 catalyst grains can also participate in hydrogen transfer, cracking, and other side reactions over the strong acid sites. Also, the generated aromatic products can also be further undesirably isomerized and deep alkylated on adjacent catalyst grains, resulting in the complexity of product composition and low selectivity of the target product. In addition, the second reaction of the hydrocarbon molecules on the external surface of the ZSM-5 grains is not restricted by space, and the molecule size of hydrocarbons could be infinitely increased . Especially for aromatics with a large molecular size, they tend to aggregate and react deeply with methanol under the action of external acid sites and eventually transform into coke species on the external surface to block the acid sites and channels, resulting in catalyst inactivation. …”
Section: Introductionmentioning
confidence: 99%